PEMBUATAN SUSU BETON SEBAGAI PENCEGAHAN NEW STUNTING PADA 1000 HARI PERTAMA KEHIDUPAN - Arum Meiranny; Muliatul Jannah; Joko Wahyu Wibowo (LPPM Universitas Bina Bangsa, 2023)
Prevention of New Stunting start from pregnancy, given the importance of the first 1000 days of life (HPK) by optimizing nutrition. One of the causes of new stunting is anemia. So it needs an innovation product that can increase the hemoglobin of pregnant women. One of them is Aren Concrete Milk. The problem of partners is the high stunting rate, which is 19.7%. That is because the public knowledge is not yet optimal about the importance of 1000 HPK. The transfer of science and technology provided is to provide training for making palm concrete milk. The training was conducted by gathering the mothers of entrepreneurial groups at the Gondang Village Hall, which amounted to 15. The activity was carried out twice, namely October 12, 2022 and November 12, 2022. The solution to this problem aims to make Aren Concrete Milk Innovation products. The form of science and technology transfer begins with the delivery of stunting material and then the demonstration of making palm concrete milk. Participants also practice the making of Aren Concrete Milk at the time of implementation, so that the skills of participants in making Aren concrete milk products can be seen